2016
DOI: 10.1038/ncomms12739
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of acoustic size exaggeration in terrestrial mammals

Abstract: Recent studies have revealed that some mammals possess adaptations that enable them to produce vocal signals with much lower fundamental frequency (F0) and formant frequency spacing (ΔF) than expected for their size. Although these adaptations are assumed to reflect selection pressures for males to lower frequency components and exaggerate body size in reproductive contexts, this hypothesis has not been tested across a broad range of species. Here we show that male terrestrial mammals produce vocal signals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 68 publications
10
129
2
Order By: Relevance
“…It is important to note that while many studies have found a relationship between fundamental frequency and body size in several species (e.g., Bowling et al, 2017;Charlton & Reby, 2016;Gingras, Boeckle, Herbst, & Fitch, 2013;Hauser, 1993;Wallschläger, 1980), others have not (e.g., Patel, Mulder, & Cardoso, 2010;Rendall, Kollias, Ney, & Lloyd, 2005;Sullivan, 1984). As noted by Bowling et al (2017), a relevant factor seems to be the range in body sizes 16 The authors theorize that two separate, but potentially related, processes may be at work.…”
mentioning
confidence: 99%
“…It is important to note that while many studies have found a relationship between fundamental frequency and body size in several species (e.g., Bowling et al, 2017;Charlton & Reby, 2016;Gingras, Boeckle, Herbst, & Fitch, 2013;Hauser, 1993;Wallschläger, 1980), others have not (e.g., Patel, Mulder, & Cardoso, 2010;Rendall, Kollias, Ney, & Lloyd, 2005;Sullivan, 1984). As noted by Bowling et al (2017), a relevant factor seems to be the range in body sizes 16 The authors theorize that two separate, but potentially related, processes may be at work.…”
mentioning
confidence: 99%
“…The size exaggeration hypothesis posits that some taxa evolve to produce vocal signals with much lower fundamental frequency (f 0 ) and/or formant frequency spacing (Δf) than expected for their size (Fitch, 2000a;Charlton and Reby, 2016). This is thought to be a way of exaggerating body size relative to other species, as lower-frequency sounds are generally associated with bigger body size across species Vol.…”
Section: Sexual Selection and The Size Exaggeration Hypothesismentioning
confidence: 99%
“…This is thought to be a way of exaggerating body size relative to other species, as lower-frequency sounds are generally associated with bigger body size across species Vol. 126, 2018 (Morton, 1975;Hauser, 1993;Fitch and Hauser, 1998;Fitch, 2010;Charlton and Reby, 2016). By lowering formant frequencies, and formant dispersion, air sacs are likely to play a key role in size exaggeration.…”
Section: Sexual Selection and The Size Exaggeration Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…This repeated convergent evolution of a descended larynx suggests some consistent selective force, and none of these other mammals produce speechlike variation in formant patterns. The current leading hypothesis is that a descended larynx, by elongating the vocal tract and lowering all formant frequencies, enables callers to mimic the formants of a larger animal and thus to acoustically exaggerate their size (Charlton & Reby 2016, Fitch & Reby 2001. Playback experiments, using resynthesized vocalizations, have verified this "size exaggeration" hypothesis in several species (Charlton et al 2012, Reby et al 2005.…”
Section: Peripheral Components Of Speech Productionmentioning
confidence: 99%